Industrial Growth Path under the Restriction of Water Resources in China - Xue, H. (2020)
Resources and environmental constraints are important problems need to be solved in the process of industrial development, especially in the critical period of industrial transformation and upgrading in China. So the perspective of the restriction of water resources was selected to analyze the industrial growth path. The results show that it is possible to realize stable industrial development, but the ratio of water resources growth rate and the human capital growth rate should be less than the ratio of human capital output flexibility and water output flexibility. Meanwhile, water resources elasticity coefficient should be further increased to improve the contribution of unit water consumption for industrial growth, so the industrial water use efficiency be improved was one of the most important aspects. The above results could provide theory and method for related department to set up industrial development and water resources utilization plans.